أداء الإطارات البيتونية المسلحة المملوءة بجدران البلوك الحاوية على فتحات تحت تأثير الحمولات الجانبية في مستويها - تريكية, علي (Latakia University Journal -Engineering Sciences Series, 2019)
The objective of this study is to conduct an analytical study to verify the effectiveness of the non-reinforced concrete walls containing the openings of reinforced concrete frames in lifting the resistance of these tires to the lateral loads in their level. Several previous studies have confirmed the contribution of the block walls to bear part of the side loads and raise the tire resistance The reinforced concrete is the result of forming a diagonal pressure field in the block wall, making it behave like a pressure-forming element. The effect of these walls is usually neglected by engineers, designers or engineers who wish to renovate the buildings, considering only its architectural function, while taking the structural sentence, ignoring the resistance and hardness of the walls. Its resistance to tensile strength is weak and its behavior is fragile and it has low resistance to coupling outside its level. Due to the presence of holes in these walls due to service purposes, we examined this situation in our research paper. Where we examined the case of a Betuni armed frame surrounded by a concrete block wall with openings, subject to side loads in the level. Various openings for these openings have been adopted. The openings for doors and windows have been adopted, and multiple openings for these openings have been adopted for the dimensions of the wall. The vacancy ratios were adopted at 7%, 22%, 34% for door openings, and 7%, 22%, 34% , 40% for window condition. Different positions were also adopted for these openings, namely the case of the aperture and the center aperture. In this paper, a numerical study was carried out using the method of limited elements by the structural program (ABAQUS, V6.12-1) under the influence of lateral loads at its level, where a linear numerical analysis was carried out that takes the non-linear effect of material By applying periodic transitions in the level of permissible for the reinforced concrete frame. The study showed the importance of the participation of the non-armed block walls for reinforced concrete frames and their contribution to bearing side loads and increasing the resistance of concrete frames and reducing their Displacement. The presence of the wall positively affects the behavior of the frame and the presence of the openings affect the behavior of this frame and lead to increase its resistance compared to resistance when It was empty, and this effect decreases with increasing openings in the wall. يهدف هذا البحث إلى إجراء دراسة تحليلية للتحقق من فعالية جدران البلوك البيتونية غير المسلحة الحاوية على فتحات المالئة للإطارات البيتونية المسلحة في رفع مقاومة هذه الإطارات على الأحمال الجانبية في مستويها حيث أكدت العديد من الدراسات السابقة مساهمة جدران البلوك في تحمل جزء من الأحمال الجانبية ورفع مقاومة الإطارات البيتونية المسلحة نتيجة تشكل حقل ضغط قطري في جدار البلوك يجعله يسلك سلوك عنصر تربيط يعمل على الضغط. يتم عادة إهمال تأثير هذه الجدران من قبل المهندسين المصممين أو المهندسين الراغبين بإعادة ترميم الأبنية معتبرين فقط الوظيفة المعمارية لها مع أخذ احمالها على الجملة الإنشائية متجاهلين ما تقدمه هذه الجدران من مقاومة وصلابة للإطارات المحيطة بها، وبسبب عدم القدرة على تحديد خواص مقاومة هذه الجدران وبسبب كون مقاومتها على الشد مقاومة ضعيفة وسلوكها سلوكاً هشاً وهي تتمتع بمقاومة منخفضة للانقلاب خارج مستويها. ونظراً لوجود الفتحات في هذه الجدران بسبب الأغراض الخدمية قمنا بدراسة هذه الحالة في ورقتنا البحثية هذه. حيث قمنا بدراسة حالة إطار بيتوني مسلح يحيط بجدار من البلوك الاسمنتي يحتوي على فتحات، يخضع لحمولات جانبية في مستويه. تم اعتماد أشكال مختلفة لهذه الفتحات حيث اعتمد حالة فتحة أبواب ونوافذ، وتم اعتماد نسب متعددة لهذه الفتحات بالنسبة لأبعاد الجدار حيث اعتمدت نسب الفراغ 7% , 22 %, 34% من أجل حالة فتحات الأبواب، ونسب الفراغ 7%, 22%, 34%, 40% من أجل حالة النوافذ. كما تم اعتماد مواقع مختلفة لهذه الفتحات وهي حالة الفتحة الطرفية وحالة الفتحة الوسطية. تم في هذا البحث إجراء دراسة عددية باســــــتخدام طريقة العناصر المحدودة بواســــطة البرنامج الإنشــــائي (ABAQUS ,V6.12-1) تحت تأثير الأحمال الجانبية في مستويها , حيث تم إجراء تحليل عددي لاخطي يأخذ تأثير لا خطية المادة ( Material Non-Linearity ) بعين الاعتبار وذلك بتطبيق انتقالات دورية في مستوي جائز الإطار البيتوني المسلح . بينت الدراسة أهمية مشاركة جدران البلوك غير المسلحة المالئة لإطارات البيتون المسلح ومساهمتها في تحمل الأحمال الجانبية وزيادة مقاومة الإطارات البيتونية وتخفيض انتقالاتها، وتبين أن وجود الجدار يؤثر بشكل ايجابي على سلوك الإطار ويؤدي إلى رفع مقاومته مقارنةً مع مقاومته عندما كان فارغاً، وإن وجود الفتحات يؤثر على سلوك هذا الإطار ويتناقص هذا التأثير مع ازدياد نسب الفتحات في الجدار.